19th Annual Fresno County Legal Secretaries Association Annual Bosses' Night Honoring Gaspar Magarian - Watkins, Howard::::::::: (1987)
1987 Legal Secretary of the Year Joan Kleinsteuber, and program emcee Justice Hollis Best